Acceptability of Peer Support for People With Schizophrenia in Chennai, India: A Cross Sectional Study Amongst People With Lived Experience, Caregivers, and Mental Health Professionals - Sims, Sonia; Hepsipa Omega Juliet, S.; Joseph, Jainey; Gopal, Subhashini; Raghavan, Vijaya; Venkatraman, Lakshmi; Padmavati, Ramachandran (Frontiers in Psychiatry, 2022)
Introduction Establishing structured peer support in mental health, particularly for people with schizophrenia, as a psychosocial intervention is early in low and middle-income countries like India. Before implementing and understanding the effectiveness of peer support service and which mode of peer support delivery will be suitable for our culture, our study aimed to understand if peer support would be accepted by the different participants like persons with schizophrenia, caregivers and mental health professionals in a tertiary care center in Chennai, India. Methods The study was conducted at the outpatient department (OPD) of a tertiary psychiatric care facility in Chennai, India. A cross-sectional study method was used. Consecutive persons diagnosed with schizophrenia and caregivers of persons with schizophrenia, who attended the outpatient department, and mental health professionals within and outside the facility who met the inclusion and exclusion criteria participated in the study. A structured questionnaire purposefully developed for the study was administered to the different study participants. Descriptive statistics were used to analyze the data. Categorical variables were expressed as frequency and percentages, while the continuous variables were expressed as mean and standard deviation. Results A total of 155 participants (52 persons with schizophrenia, 50 caregivers and 53 mental health professionals) completed the survey. The majority of the participants (90.4% of persons with schizophrenia, 86% caregivers and all mental health professionals) welcomed peer support interventions. The participants wanted peers to help persons with schizophrenia achieve personal goals to enhance their mental health and day to day living with an emphasis on independent living and interpersonal and social relationships and help them achieve medication and treatment-related goals toward recovery. Understanding the role of a peer support volunteer and transitioning from a “person with schizophrenia” to a “peer support volunteer” by persons with schizophrenia was thought most challenging. Conclusion The results highlight the potential acceptability of peer support across several stakeholders in the care of schizophrenia in a low and middle-income country context. The results may guide the implementation of a peer support volunteer programme as an essential mechanism of delivering psychosocial interventions for persons with schizophrenia.